Bordering the other, building the nation-state: positioning the refugee as a subject of school knowledge - Jarratt, Lindsay (Journal of curriculum studies, 2020)
The refugee has become part of the scholarly discourse of schooling, largely centring considerations of psychological trauma that refugee children may have experienced. However, the role that schools play in creating, replicating, or transforming a national discourse of refugees-and by extension, (inter)national identity and citizenship-at the curricular level remains less explored. This exploratory study maps language-in-use from secondary school lesson plans about refugees, collected from United States teaching contexts. Utilizing qualitative and critical discourse analysis (CDA) methods to analyse discursive strategies employed in these lessons, tensions between the espoused objectives and pedagogical procedures of the curricula emerge. Findings reveal a narrative that enacts a national identity and supremacy within a global discourse, maintaining boundaries between citizens and refugees-between 'us' and the Other.